Information Freedom - Legal Category of Formation of Basis of Civil Society - URAKOVICH, MUKHAMMADIEV JABBOR; MAKHMUT, MAMATOV; AKBAROVICH, BAHRAMOV SAYFIDDIN; SHODIEVICH, SIROZHOV BURKHON; ERBAZAROVNA, TILLAEVA MUYASSAR (The journal of contemporary issues in business and government, 2021)
Strengthening of the noticeable influence of the information sphere on the life of a person, on the activities of the state and society has turned into one of the features of social development of the second half of the twentieth century and the beginning of the twenty-first century. This is determined, firstly, by the scientific and technological revolution in the field of computer technology and telecommunications, new achievements significantly increasing the effectiveness of activities related to information, and secondly, human rights and freedoms in the field of human information activities are noted as the main values of modern civilization. The protection of human rights and freedoms in the sphere of human information activities, the improvement of the national information infrastructure and the provision of its stable activities occupy an important place in the system of public interests as an information element reflecting the interests of the development of the "information" national economy. The recognition of truthfulness and fairness, clarity, openness, freedom of expression and information in the first place, depends on the extent to which freedom of expression and freedom of speech are provided in all the processes taking place in society and reforms. Ensuring freedom of speech and information, openness, clarity of all reforms and processes implemented in most cases depends on how freely and democratically the press and other mass media cover the ongoing processes, since freedom of speech, freedom of media activity is a special sign of democracy. The article analyzes the main approaches to ensuring freedom of information of the country, formulated the goal, tasks, functions, principles of ensuring freedom of information of the country. More specifically, we will dwell on the legal aspect of ensuring freedom of information.